2015
DOI: 10.1037/prj0000111
|View full text |Cite
|
Sign up to set email alerts
|

Recovery narrative photovoice: Feasibility of a writing and photography intervention for serious mental illnesses.

Abstract: Findings support the feasibility and acceptability of the Recovery Narrative Photovoice for individuals with serious mental illnesses. These results reflect the potential for using this intervention in psychiatric rehabilitation settings to facilitate recovery-related outcomes, including empowerment, positive identity, and community integration. Future research will require a replication of pre-post assessment of this intervention to further establish the efficacy of this program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 8 publications
1
71
0
Order By: Relevance
“…Five of the included papers recommended photovoice, art-making and exhibition as interventions used to construct recovery (56)(57)(58)(59)(60). The photovoice, artmaking and exhibition are used to achieve recovery, empowerment, community integration (56,58,59) and share di cult experiences non-verbally (57). The intervention aims to explore, document and share ideas about recovery.…”
Section: Recovery Narrative Photovoice Art-making and Exhibitionmentioning
confidence: 99%
See 3 more Smart Citations
“…Five of the included papers recommended photovoice, art-making and exhibition as interventions used to construct recovery (56)(57)(58)(59)(60). The photovoice, artmaking and exhibition are used to achieve recovery, empowerment, community integration (56,58,59) and share di cult experiences non-verbally (57). The intervention aims to explore, document and share ideas about recovery.…”
Section: Recovery Narrative Photovoice Art-making and Exhibitionmentioning
confidence: 99%
“…The intervention aims to explore, document and share ideas about recovery. It involves the construction of text with photographs through the exhibition and large group discussion (56,58,59). More importantly, the intervention helps to avoid the stigma that is associated with the conventional process of delivering mental health services (60).…”
Section: Recovery Narrative Photovoice Art-making and Exhibitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested that the recovery of consumers could be achieved through the implementation of interventions such as vocational rehabilitation, integrated rehabilitation and recovery narrative photovoice, art‐making, and exhibition services as well as leisure and recreational activities (Burns et al 2008; Crosse 2003; Malinovsky et al 2013; Mizock et al 2015; Raeburn et al 2016). These services are implemented through collaboration or partnership between MHPs, consumers, and their family caregivers.…”
Section: Introductionmentioning
confidence: 99%